2003
DOI: 10.1002/marc.200390089
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Poly(methyl methacrylate) Nanosize Particles by Differential Microemulsion Polymerization

Abstract: Poly(methyl methacrylate) nanosize particles were synthesized by a differential microemulsion polymerization process. Sodium dodecylsulfate and ammonium persulfate were used as the surfactant and initiator, respectively. The effects of reaction conditions on the particle size have been investigated. A particle size of less than 20 nm in diameter has been achieved with surfactant/monomer and surfactant/water weight ratios of 1:18 and 1:120, i.e. much milder conditions than those previously reported in the liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
80
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(86 citation statements)
references
References 15 publications
5
80
1
Order By: Relevance
“…To explore a practical technical route in which the surfactant amount required could be significantly decreased and by which the nanoparticle size could be controlled, a differential microemulsion polymerization was proposed, [7] in which the monomer feed was provided in very small drops and the time interval between drops was very short. It was indicated that a lower amount of surfactant was needed in this system compared to with other methods reported in the literature.…”
Section: Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…To explore a practical technical route in which the surfactant amount required could be significantly decreased and by which the nanoparticle size could be controlled, a differential microemulsion polymerization was proposed, [7] in which the monomer feed was provided in very small drops and the time interval between drops was very short. It was indicated that a lower amount of surfactant was needed in this system compared to with other methods reported in the literature.…”
Section: Communicationmentioning
confidence: 99%
“…[7][8][9] This promising phenomenon was attributed to the mechanism of homogeneous nucleation because a water soluble initiator was used and the monomer concentration in the reaction system was kept at a starving level. [7] This communication reports on new discoveries when the differential microemulsion polymerization method is applied to the synthesis of PMMA nanoparticles with an oil soluble initiator, in which the particle nucleation is believed to happen in micelles and follow a heterogeneous nucleation mechanism, rather than occurring in the aqueous phase and following a homogeneous nucleation mechanism. The effect of surfactant concentration on particle size and conversion, as well as on molecular weight is investigated.…”
Section: Communicationmentioning
confidence: 99%
“…In this study, hybrid nanoparticles comprised of the nTiO 2 core and PS shell were synthesized via in situ differential microemulsion polymerization, which is an efficient process that can produce organic-inorganic hybrid nanoparticles with a core-shell morphology of much smaller diameter (<50 nm) than those obtained from the conventional emulsion polymerization, and requires much lower amount of surfactant than that used in the pristine microemulsion polymerization [6,27,28]. However, prior to encapsulating, the nTiO 2 was modified by a polymerizable silane coupling agent aimed at bonding PS and nTiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, they have found applications in biomedical fields such as bio-imaging, drug delivery and diagnostics. PNP-based materials with unique physical and chemical characteristics might become future commands for the progress of new nanomaterials [4][5][6][7]. As a contribution to updating the state of knowledge and due to importance of PNPs, the present review focuses on PNPs.…”
Section: Introduction To Polymer Nanoparticles (Pnp)smentioning
confidence: 99%